Pirolisis Kayu Akasia (Acacia Mangium) Menjadi Bio-Oil Menggunakan Katalis Ni/NZA Dengan Variasi Pengembanan Logam Dan Rasio Katalis - Sari Rahma Yanti; Syaiful Bahri; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The problems that currently appear in Indonesia is the energy crisis, especially fuel oil (BBM). Fuel derived from crude oil (fossil fuel) that can not be updated, so the next few years is expected to be deprived community will fuel. To overcome these problems needed alternative energy sources is the use of renewable biomass into bio-oil. Bio-oil is produced from biomass through pyrolysis. The purpose of this research was determine the effect of the impregnation percentage of Ni metal and ratio of catalyst Ni/NZA on the yield of bio-oil and determine the physical and chemical characteristics of bio-oil. Pyrolysis using 50 grams acacia wood, 500 ml silinap and Ni/NZA catalyst with variations of the impregnation percentage of Ni metal 0%, 1%, 3%, 6% and the variation ratio of catalyst Ni/NZA 3%, 6% and 9% of the biomass with a stirring speed of 300 rpm and a temperature of 320ºC for 120 minutes. In this research, the highest yield on the variation of the impregnation percentage of metal 1% and the ratio of catalyst 9% of the biomass amounted to 77,85%. Characteristics of bio-oil obtained were density 0,865 gr/ml, viscosity 1,621 cSt, acid number 88,115 mg NaOH/gr sample, and the flash point 43oC. The results of GC-MS analysis, the dominant chemical components in the bio-oil were 1,3-Pentadiene, 2,4-Dimethyl (1,591%), 3-Octyne,7-methyl (1,591%), 4-Nonene,5-butyl (7,846%), Dodecane,5,8-diethyl (3,531%) and 1-Tricosanol (7,158%).Keywords: Bio-oil, pyrolysis, catalyst Ni/NZA, acacia wood